Pro JavaFX 8 a definitive guide to building desktop, mobile, and embedded Java clients - Vos, Johan (Apress, 2014)
This book provides code examples that explore the exciting new features provided with JavaFX 8 which comes as part of Oracle's new Java (SE) 8 release. The reader will learn how to: get started with JavaFX, including downloading the SDK and available tools; express user interfaces with SceneBuilder and FXML; use property binding to keep the UI easily in sync with the model; use the rich set of JavaFX UI controls, charts, shapes, effects, transformations, and animations to create stunning, responsive, user interfaces; use the powerful JavaFX layout classes to define the user interface in a cross-platform fashion; leverage the observable collection classes to observe changes in, and bind to, Java collections; use the JavaFX media classes to play audio and video; interact with external application services to create an enterprise application with JavaFX; use the JavaFX API with alternative languages such as Scala and Groovy; use Java on embedded, mobile, and tablet devices. --
Includes bibliographical references and index. - Online resource; title from PDF title page (SpringerLink, viewed August 5, 2014)
Keywords: JavaFX (Electronic resource); Java (Computer program language); Graphical user interfaces (Computer systems); Application software -- Development; Internet programming; Java (Langage de programmation); Interfaces graphiques (Informatique); Logiciels d'application; Développement; Programmation Internet; Application software; Development